2020
DOI: 10.1163/23641177-bja10011
|View full text |Cite
|
Sign up to set email alerts
|

Inequity and Cultural Differences in Out-of-School Science Education: The Case of the Arab Minority in Israel

Abstract: This paper examines the gap between Jewish and Arab students in Israel in the context of learning in informal environments. I attempted to understand whether the difference is a matter of inequity in terms of resource allocation and opportunities provided to the schools. I present the socio-historical-political context and the current situation, based on formal documents. To gain an insiders’ views, I interviewed five Arab science educators and an Arab superintendent. These conversations highlighted the cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In addition, it seems that despite growing research in the field, few researchers have examined how these informal learning environments are supposed to close the gap between the present situation and the desired one. Our study addresses the gap identified by Feinstein and Meshoulam (2014) and Dawson (2017), and continues previous work on equality in the context of science education in Israel (Sedawi, Ben Zvi Assaraf, & Cwikel, 2014; Shaby et al, 2017a; Tal, 2020). Our study of students from (Jewish) underserved communities visiting a science center over three consecutive years found that the instruction those students get in a museum is commonly technical, or such that focuses mainly on engaging them with the exhibit emotionally rather than encouraging them to understand phenomena and principles (Shaby, Ben Zvi Assaraf, & Tal, 2017b).…”
Section: Theoretical Frameworksupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, it seems that despite growing research in the field, few researchers have examined how these informal learning environments are supposed to close the gap between the present situation and the desired one. Our study addresses the gap identified by Feinstein and Meshoulam (2014) and Dawson (2017), and continues previous work on equality in the context of science education in Israel (Sedawi, Ben Zvi Assaraf, & Cwikel, 2014; Shaby et al, 2017a; Tal, 2020). Our study of students from (Jewish) underserved communities visiting a science center over three consecutive years found that the instruction those students get in a museum is commonly technical, or such that focuses mainly on engaging them with the exhibit emotionally rather than encouraging them to understand phenomena and principles (Shaby, Ben Zvi Assaraf, & Tal, 2017b).…”
Section: Theoretical Frameworksupporting
confidence: 80%
“…With this regard, a promising initiative of the Ministry of Education “Meaningful Science Experiences” is offered now to schools based on SES criteria, meaning that schools serving lower SES communities are prioritized and get to visit the museums more than schools serving higher SES communities. Recent information gathered from the largest science center in the country, for another study on equity and learning in informal settings, shows that a much higher percentage of Arab schools get to participate in this initiative (Tal, 2020). Further information, received from the Technoda, which is located in an underprivileged community, acknowledges that schools from poor communities, Jewish and Arab alike get special discounts to allow every student to enjoy the MSBE.…”
Section: Discussionmentioning
confidence: 99%
“…STEAM education has to provide opportunities and spaces to students, specifically those from underrepresented groups and girls, to critically reflect and challenge existing social structures of oppression and subjugation. Studies in science education have clearly shown that when given space and environment to leverage science to explore socioculturally related issues, students seem to show more significant affinity to science and are more engaged (Arnold & Clarke, 2014;Bruna, 2009; Osborne & Calabrese Tal, 2020;Upadhyay & Albrecht, 2011;Upadhyay et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The Arab minority constitutes approximately 19% of the population in Israel (Central Bureau of Statistics 2020), and is considered a non-assimilating minority that has limited access to the opportunity structure (Agbaria et al 2015;Al-Krenawi 2016;Al-Haj 1995). Consequently, the Arab minority has a lower standing in all aspects of socioeconomic status (including education, occupation, and income) compared with the Jewish majority (Agbaria et al 2015;Al-Haj 1995;Semyonov and Lewin-Epstein 1994;Tal 2020).…”
Section: Science Education In the Arab Sector In Israel-ethnic Perspectivesmentioning
confidence: 99%